2006
DOI: 10.1002/cncr.21833
|View full text |Cite
|
Sign up to set email alerts
|

The influence of comorbidities, age, and performance status on the prognosis and treatment of patients with metastatic carcinomas of unknown primary site

Abstract: BACKGROUNDThe authors investigated how comorbidities, age, and performance status were related to the choice of chemotherapy and to the prognosis of patients with carcinomas of unknown primary site (CUP).METHODSPatients in Northern Alberta who were diagnosed with CUP during 2000 to 2003 were included (n = 389 patients). Survival was compared by age at diagnosis (ages <65 years, 65‐74 years, and >75 years), comorbidity score (Adult Comorbidity Evaluation‐27 [ACE‐27] scores of 0‐1 and >2), performance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 31 publications
6
23
0
1
Order By: Relevance
“…There is inherent, small error (5/1000 records) [27] in our probabilistic record linkage that is not expected to differ for cases and controls. There is also the potential for confounding by performance score, site(s) of metastases (likely >1 for CUP) [28][29][30], type of specialist (e.g. surgeon, oncologist), and comorbid conditions that were not captured by the administrative records.…”
Section: Discussionmentioning
confidence: 99%
“…There is inherent, small error (5/1000 records) [27] in our probabilistic record linkage that is not expected to differ for cases and controls. There is also the potential for confounding by performance score, site(s) of metastases (likely >1 for CUP) [28][29][30], type of specialist (e.g. surgeon, oncologist), and comorbid conditions that were not captured by the administrative records.…”
Section: Discussionmentioning
confidence: 99%
“…obtienen una supervivencia a los 5 años del 27% en una serie de 137 sujetos mayores de 70 años sometidos a IIA, equiparable a la del grupo de control de menor edad; sorprendentemente, los autores no comunican diferencias significativas al analizar específicamente la mortalidad por causas extrahepáticas en ambos grupos de pacientes (13). Desgraciadamente, el carácter retrospectivo de nuestro estudio dificulta la valoración de determinados aspectos, como la situación funcional (performance status) basal del paciente o su comorbilidad, de relevancia demostrada tanto en el pronóstico del paciente oncológico (29) como en la elección y tolerancia de su tratamiento (30). Por ejemplo, la variabilidad observada en nuestra cohorte respecto a los niveles séricos de albúmina (2,9 g/dl en ancianos frente a 3,2 g/dl en no ancianos) resultaría atribuible, más allá de diferencias en la hepatopatía crónica de base de ambos grupos, a factores propios de la edad avanzada, tales como la malnutrición u otras comorbilidades digestivas.…”
Section: Discussionunclassified
“…It is our hope to find favorable prognostic factors for elderly CUP patients requiring treatment. There have been many studies that have revealed different prognostic factors to predict the outcome of CUP [17,18,19], but this is the first study to analyze elderly CUP patients .…”
Section: Discussionmentioning
confidence: 99%